Larvae of Amphipsyche species (Trichoptera: Hydropsychidae) from Thailand - Peumwarunyoo, Pronthip; Prommi, Taeng-On (Zootaxa, 2013)
Morphological characters and scanning electron microscope images of the larvae of Amphipsyche meridiana and A. gratiosa are given. Pupal identifications are based on genitalic features in common with described adults, and larvae were associated with the pupae based on residual larval sclerites captured in the pupal case. Herein, the final larval instar is described, diagnosed, and photographed for each species.